Silencing of Mitochondrial Trifunctional Protein A Subunit (HADHA) Increases Lipid Stores, and Reduces Oviposition and Flight Capacity in the Vector Insect Rhodnius prolixus - Arêdes, Daniela S.; De Paula, Iron F.; Santos-Araujo, Samara; Gondim, Katia C. (Frontiers in Insect Science, 2022)
Rhodnius prolixus is an obligatory hematophagous insect, vector of Chagas disease. After blood meal, lipids are absorbed, metabolized, synthesized, and accumulated in the fat body. When necessary, stored lipids are mobilized, transported to other organs, or are oxidized to provide energy. Mitochondrial β-oxidation is a cyclic conserved pathway, where degradation of long-chain fatty acids occurs to contribute to cellular energetic demands. Three of its reactions are catalyzed by the mitochondrial trifunctional protein (MTP), which is composed by hydroxyacyl-CoA dehydrogenase trifunctional multienzyme complex subunits alpha and beta (HADHA and HADHB, respectively). Here, we investigated the role of HADHA in lipid metabolism and reproduction of Rhodnius prolixus females. The expression of HADHA gene (RhoprHadha) was determined in the organs of starving adult insects. The flight muscle and ovary had higher expression levels when compared to the anterior and posterior midguts or the fat body. RhoprHadha gene expression was upregulated by blood meal in the flight muscle and fat body. We generated insects with RNAi-mediated knockdown of RhoprHadha to address the physiological role of this gene. RhoprHadha deficiency resulted in higher triacylglycerol content and larger lipid droplets in the fat body during starvation. After feeding, lifespan of the knockdown females was not affected, but they exhibited a decrease in oviposition, although hatching was the same in both groups. Silenced females showed lower forced flight capacity than the control ones, and their fat bodies had lower gene expression levels of Brummer lipase (RhoprBmm) and long-chain acyl-CoA synthetase 2(RhoprAcsl2). Taken together, these findings indicate that HADHA is important to guarantee successful reproduction and efficient mobilization of lipid stores during starvation and flight.